Pemberdayaan Remaja Putri: Penguatan dalam Pencegahan Anemia di Pondok Pesantren Al Hidayah - Tina Yuli Fatmawati; Andicha Gustra Jeki; Maryam Novitasari; Nel Efni (Jurnal Abdimas Kesehatan (JAK), 2026)
One of the nutritional problems often experienced by adolescent girls is anemia. Adolescent girls are categorized as having anemia if the hemoglobin (Hb) level in the blood is less than 12 gr/dl. The type of anemia that often occurs is iron deficiency anemia, which is generally caused by blood loss during menstruation and increased iron requirements during puberty. As an effort to overcome this, a sustainable anemia prevention program was designed through the formation and strengthening of the Anemia Ambassador Team. This strengthening is carried out by providing education about anemia to adolescent girls. The purpose of this strengthening is to form peer cadres who play an active role in the prevention and control of anemia in the school environment on an ongoing basis. This activity was carried out in Al Hidayah Islamic Boarding School, Jambi City. The target of the activity was 13 people, with the FGD method and guidance. The results of the community service were obtained by forming ORSADA Cadres selected from peers who are expected to have a strong influence and be able to convey information about anemia, an increase in the knowledge of cadres about preventing anemia